2010
DOI: 10.1007/s10067-009-1348-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between clinical and ultrasonographic assessment in patients with erosive osteoarthritis of the hands

Abstract: The objective of this study is to assess the reliability of clinical examination in patients with erosive osteoarthritis (EOA). Eighteen patients with EOA underwent clinical examination for joint tenderness, bony swelling, and inflammation by two independent, blinded assessors. All patients were also examined by ultrasound (US) by an independent radiologist. The inter-observer agreement was moderate for bony swelling and joint tenderness and fair for joint inflammation (kappa = 0.513, 0.448, and 0.402, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 34 publications
3
33
0
Order By: Relevance
“…In addition, radiographic features of OA do not concord with the symptoms of OA [Felson, 2004;Hannan et al 2000]. US has been shown to be more sensitive than clinical examination in the detection of joint inflammation in patients with erosive OA [Koutroumpas et al 2010]. Synovitis detection in OA is considered important because its presence has been shown to be associated with pain [Hill et al 2001].…”
Section: Osteoarthritismentioning
confidence: 99%
“…In addition, radiographic features of OA do not concord with the symptoms of OA [Felson, 2004;Hannan et al 2000]. US has been shown to be more sensitive than clinical examination in the detection of joint inflammation in patients with erosive OA [Koutroumpas et al 2010]. Synovitis detection in OA is considered important because its presence has been shown to be associated with pain [Hill et al 2001].…”
Section: Osteoarthritismentioning
confidence: 99%
“…HRMSUS was able to detect sinovitis in 24.1% of patients with erosive OA and this was in agreement with other studies, although the detection of synovitis may be technically more difficult in DIP joints and synovitis can be present in nonerosive OA. As a result, HRMSUS has been used as a gold standard to evaluate the reliability of the clinical examination in detecting inflammation in patients with erosive OA [Wittoek et al, 2010[Wittoek et al, , 2011Koutroumpas et al, 2010]. US detected synovitis was associated with more severe radiological damage and decreased cartilage thickness in patients with hand OA in a limited study of 25 patients.…”
Section: Erosive Oamentioning
confidence: 98%
“…However, the disease is frequently accompanied by inflammatory flares [154,155], and a variety of findings suggest that this inflammatory process contributes at least to the progression of OA [29]. Also, in different studies analyzing the effect of mechanical injury, chondrocytes have been shown to exert an increased expression of inflammatory mediators and stress response factors [49].…”
Section: Disease-modifying Approaches In Osteoarthritismentioning
confidence: 99%